2022
DOI: 10.3389/fcell.2022.908992
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Functional Roles of Neurotrophin-4 During In Vitro Maturation of Porcine Cumulus–Oocyte Complexes

Abstract: Neurotrophin-4 (NT-4), a granulosa cell-derived factor and a member of the neurotrophin family, is known to promote follicular development and oocyte maturation in mammals. However, the physiological and functional roles of NT-4 in porcine ovarian development are not yet known. The aim of this study was to investigate the physiological role of NT-4-related signaling in the in vitro maturation (IVM) of porcine cumulus–oocyte complexes (COCs). The NT-4 protein and its receptors were detected in matured porcine C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Since the present study is the first to show the localization of neurotrophic factors and their receptors in porcine PA blastocysts, further studies are needed to confirm their localization patterns across different stages of porcine embryonic development. According to our previous study, NT-4, total-TrkB, phospho-TrkB, and p75 NTR were localized in both the nuclei and cytoplasm of porcine cumulus cells, whereas they were only localized to ooplasms of in vitro matured-porcine oocytes ( Kim et al, 2022 ). Therefore, our present study demonstrated that the localization patterns of NT-4 and its receptors are cell-type specific.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Since the present study is the first to show the localization of neurotrophic factors and their receptors in porcine PA blastocysts, further studies are needed to confirm their localization patterns across different stages of porcine embryonic development. According to our previous study, NT-4, total-TrkB, phospho-TrkB, and p75 NTR were localized in both the nuclei and cytoplasm of porcine cumulus cells, whereas they were only localized to ooplasms of in vitro matured-porcine oocytes ( Kim et al, 2022 ). Therefore, our present study demonstrated that the localization patterns of NT-4 and its receptors are cell-type specific.…”
Section: Discussionmentioning
confidence: 87%
“…Recombinant human NT-4 (450-04) was purchased from PeproTech (Rocky Hill, NJ, United States). NT-4 protein was used after being dissolved in Dulbecco’s phosphate-buffered saline (DPBS; LB001-02; WELGENE, Gyeongsan, Gyeongsangbuk-do, Republic of Korea) with 0.1% (w/v) bovine serum albumin, as previously described ( Kim et al, 2022 ). Verteporfin (HY-B0146; MedChemExpress, Princeton, NJ, United States), a yes-associated protein (YAP) inhibitor, was then dissolved in dimethyl sulfoxide (DMSO; Sigma Aldrich Corporation, St. Louis, MO, United States).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations